6c+13=7c-6c+2c

Simple and best practice solution for 6c+13=7c-6c+2c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6c+13=7c-6c+2c equation:


Simplifying
6c + 13 = 7c + -6c + 2c

Reorder the terms:
13 + 6c = 7c + -6c + 2c

Combine like terms: 7c + -6c = 1c
13 + 6c = 1c + 2c

Combine like terms: 1c + 2c = 3c
13 + 6c = 3c

Solving
13 + 6c = 3c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-3c' to each side of the equation.
13 + 6c + -3c = 3c + -3c

Combine like terms: 6c + -3c = 3c
13 + 3c = 3c + -3c

Combine like terms: 3c + -3c = 0
13 + 3c = 0

Add '-13' to each side of the equation.
13 + -13 + 3c = 0 + -13

Combine like terms: 13 + -13 = 0
0 + 3c = 0 + -13
3c = 0 + -13

Combine like terms: 0 + -13 = -13
3c = -13

Divide each side by '3'.
c = -4.333333333

Simplifying
c = -4.333333333

See similar equations:

| 0.7x-0.4(30+x)=0.2(30) | | .90x+.05(18-x)=.10(-93) | | 3t-5=1 | | x=24+-3y | | 4q+6=38 | | g=3g+3v | | -5+-4v=-17 | | 3/4-3/5x=23/20 | | 15-2m=5 | | 3x+9y=-3 | | 3u^2+2=7u | | 2k-5=-1 | | 1/3*270 | | x+3y=74 | | 3r+16=1 | | 4y-7+y+41=7y+40-5y | | 400-2x=232 | | 5x+12=3x+14 | | 11+.05(x-700)=12.70 | | 4y-7+41=7y+40-5y | | 2x+16=x+16 | | 14+0.20(x-300)=43.06 | | 2n-15/8=17/8 | | 7m^2-11n^2=7 | | 1.6+7.6(x)=x+28.4 | | 8+39=47 | | 5(z+5)-2=9z | | 1=2+-h | | -4(x+1)-2x+5=31 | | -1=3y-10 | | 3(X)+3(Y)=152 | | 3=11-2c |

Equations solver categories